Best friends forever! - Ferry, Beth (Houghton Mifflin Harcourt, 2021)
This ode to unconditional love is a brand new adventure for New York Times best-selling duo Stick and Stone, in which Stick searches for his family tree and discovers the importance of found family and forever friends.